Utilizing Zebrafish Embryos to Reveal Disruptions in Dorsoventral Patterning. Issue 6 (24th June 2021) - Dasgupta, Subham; Cheng, Vanessa; Volz, David C.
Abstract: Dorsoventral (DV) patterning is a key landmark of embryonic development that is primarily regulated by bone morphogenetic protein (BMP) signaling. Disruption of DV patterning can result in downstream effects on cell specification and organogenesis. Zebrafish embryos have been extensively used to understand signaling pathways that regulate DV patterning because zebrafish embryos develop ex utero and, in contrast to mammalian embryos, which develop in utero, can be observed in real time using brightfield and fluorescence microscopy. Embryos with disrupted DV patterning are either dorsalized or ventralized, with lack of development of head or trunk/tail structures, respectively. Although these phenotypes are typically accompanied by effects on BMP signaling, exceptions exist where some drugs or environmental chemicals can disrupt DV patterning in the absence of effects on BMP signaling. Therefore, assessments of DV patterning should be accompanied by BMP signaling–specific readouts to confirm the role of BMP disruption. Here, we describe an exposure paradigm and steps for phenotyping zebrafish embryos for two types of DV defects, dorsalization and ventralization, with a range of severities. In addition, we describe a strategy for whole‐mount immunohistochemistry of zebrafish embryos with an antibody specific for phospho‐SMAD 1/5/9 (pSMAD 1/5/9), as disruption in pSMAD 1/5/9 localization is indicative of an effect on BMP signaling. Taken together, these protocols describe an initial strategy for evaluating DV patterning defects under various experimental conditions and confirming BMP‐mediated DV patterning disruptions, which can be followed by additional studies that aim to uncover mechanisms leading to these adverse phenotypes. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Phenotyping for dorsalization and ventralization Basic Protocol 2 : Whole‐mount immunohistochemistry with antibody to phospho‐SMAD 1/5/9